Activating KIRs and NKG2C in Viral Infections: Toward NK Cell Memory? - Della Chiesa, Mariella; Sivori, Simona; Carlomagno, Simona; Moretta, Lorenzo; Moretta, Alessandro (Frontiers in Immunology, 2015)
Natural Killer cells are important players in the immune defence against viral infections. The contribution of activating Killer Immunoglobulin-like Receptors (KIRs) and CD94/NKG2C in regulating anti-viral responses has recently emerged. Thus, in the Hematopoietic Stem Cell Transplantation (HSCT) setting, the presence of donor activating KIRs may protect against viral infections, while in HIV-infected individuals KIR3DS1 in combination with HLA-Bw4-I80, results in reduction of viral progression. Since, studies have been performed mainly at the genetic or transcriptional level, the effective size, the function and the “licensing” status of NK cells expressing activating KIRs, as well as the nature of their viral ligands, require further investigation. Certain viral infections, mainly due to Human Cytomegalovirus (HCMV), can deeply influence the NK cell development and function by inducing a marked expansion of mature NKG2C+ NK cells expressing self-activating KIRs. This suggests that NKG2C and/or activating KIRs are involved in the selective proliferation of this subset. The persistent, HCMV-induced, imprinting suggests that NK cells may display unexpected adaptive immune traits. The role of activating KIRs and NKG2C in regulating NK cell responses and in promoting a memory-like response to certain viruses is discussed.